Semaphorin3B promotes an anti-inflammatory and pro-resolving phenotype in macrophages from rheumatoid arthritis patients in a MerTK-dependent manner - Martínez-Ramos, Sara; Rafael-Vidal, Carlos; Malvar-Fernández, Beatriz; Pérez, Nair; Mouriño, Coral; Pérez, Sara García; Maceiras Pan, Francisco J.; Conde, Carmen; Pego-Reigosa, Jose María; García, Samuel (Frontiers in Immunology, 2024)
Our group has previously shown that Semaphorin3B (Sema3B) is reduced in rheumatoid arthritis (RA) and plays a protective role in a mouse arthritis model. In turn, MerTK plays a protective function in murine arthritis models, is expressed by synovial tissue macrophages and is linked to remission in patients with RA. In this study, we examined the role of Sema3B in the phenotypic characteristics of RA macrophages and the implication of MerTK.Peripheral blood monocytes from RA patients were differentiated into IFN-γ (RA MØIFN-γ) or M-CSF (RA MØM-CSF) macrophages and stimulated with LPS, Sema3B or their combination. Alternatively, RA fibroblast like synoviocytes (FLS) were stimulated with RA MØIFN-γ and RA MØM-CSF supernatants. Gene expression was determined by qPCR and protein expression and activation by flow cytometry, ELISA and western blot.Sema3B down-regulated the expression of pro-inflammatory mediators, in both RA MØIFN-γ and RA MØM-CSF. We observed a similar reduction in RA FLS stimulated with the supernatant of Sema3Btreated RA MØIFN-γ and RA MØM-CSF. Sema3B also modulated cell surface markers in macrophages towards an anti-inflammatory phenotype. Besides, MerTK expression and activation was up-regulated by Sema3B, just as GAS6 expression, Resolvin D1 secretion and the phagocytic activity of macrophages. Importantly, the inhibition of MerTK and neuropilins 1 and 2 abrogated the antiinflammatory effect of Sema3B. Our data demonstrate that Sema3B modulates the macrophage characteristics in RA, inducing a skewing towards an anti-inflammatory/pro-resolving phenotype in a MerTK-dependant manner.Therefore, here we identify a new mechanism supporting the protective role of Sema3B in RA pathogenesis.